Diagnosis and Treatment of Purulent Inflammatory Skin Diseases in Children (Texas Journal of Medical Science, 2022)
The paper summarizes the general principles and standardized diagnostic clinical symptoms of inflammatory skin diseases. A general concept ofpurulentsfcin diseases in children. Describes the clinical features, diagnosis and differential diagnosis of purulent skin diseases in children.Unsubstantiated diagnostic and therapeutic strategy.